Decreased Abundance of Akkermansia muciniphila Leads to the Impairment of Insulin Secretion and Glucose Homeostasis in Lean Type 2 Diabetes (Adv. Sci. 16/2021). Issue 16 (18th August 2021) - Zhang, Jing; Ni, Yueqiong; Qian, Lingling; Fang, Qichen; Zheng, Tingting; Zhang, Mingliang; Gao, Qiongmei; Zhang, Ying; Ni, Jiacheng; Hou, Xuhong; Bao, Yuqian; Kovatcheva‐Datchary, Petia; et al.
Abstract : New Therapeutic Options for the Treatment of Diabetes In article number 2100536, Huating Li, Gianni Panagiotou, Weiping Jia, and co‐workers demonstrate lean patients with type 2 diabetes have distinct gut microbiota and bile acid profiles. The "Magician" Akkermansia muciniphila connects the gut to pancreas and liver by modulating 3β‐chenodeoxycholic acid and fibroblast growth factor 19, which sheds light on new therapeutic options for the prevention or treatment of diabetes.